Impact of Genetic and Nongenetic Factors on Body Mass Index and Waist-Hip Ratio Change in HIV-Infected Individuals Initiating Antiretroviral Therapy. (22nd January 2020) - Barceló, Catalina; Guidi, Monia; Thorball, Christian W; Hammer, Christian; Chaouch, Aziz; Scherrer, Alexandra U; Hasse, Barbara; Cavassini, Matthias; Furrer, Hansjakob; Calmy, Alexandra; Haubitz, Sebastian; Bernasconi, Enos; et al.
Abstract: Objective: There is limited data on abdominal obesity and the influence of genetics on weight change after antiretroviral therapy (ART) initiation. We assessed body mass index (BMI) and waist hip ration (WHR) change over time in the Swiss HIV Cohort study (SHCS). Methods: Mixed-effects models characterizing BMI and WHR change over time in 1090 SHCS participants initiating ART between 2005 and 2015 were developed and used to quantify the influence of demographics, clinical factors, and genetic background. Results: Individuals with CD4 nadir <100 cells/µL gained 6.4 times more BMI than individuals with ≥200, and 2.8 times more WHR than individuals with ≥100 ( P < .001) during the first 1.5 and 2.5 years after ART initiation, respectively. The risk of being overweight or obese after 1.5 years increased with CD4 nadir <100 cells/µL compared to 100–199 (odds ratio [OR], 2.07; 95% confidence interval [CI], 1.63–2.74) and ≥200 (OR, 1.69; 95% CI, 1.26–2.32), persisting after 10 years of ART. The risk of abdominal obesity after 2.5 years increased with CD4 nadir <100 compared to ≥100 (OR, 1.35; 95% CI, 1.17–1.54 [in men]; OR, 1.36; 95% CI, 1.18–1.57 [in women]), persisting after 10 years of ART. No significant differences were found across antiretroviral drug classes or genetic scores. Conclusions: The risk of general and abdominal obesity increased with CD4 nadir <100 cells/µL. Based on our results, including the genetic background would not improve obesity predictions in HIV-infected individuals.